Perbandingan Validitas Hadis dalam Shahih Al-Bukhari dan Al-Adab Al-Mufrad: Suatu Tinjauan Ilmiah - Fuhair Annahdhi; Romlah Abubakar Askar (AL-BAYAN INSTITUTE, 2025)
The validity of hadith is a fundamental aspect of the hadith study, particularly in a diverse field of keispage as the reference to the authentic Rasulullah saw. The priest al-Bukhari, the central figure in the isthmian, produced two notable works: Shahih al-Bukhari and al-Adab al-Mufrad. Both are structured with different methodologies and orientation. Such strict standards of validity are consistently applied by shahih al-bukhari, which contains only hadis-hadith with shahih degrees, while the hadith with varying degrees, from shahih to hasan and in part part of the multiplicity (dhaif), contained in al-Adab al-Mufrad asa thematic work on adab. The goal of this research is to compare the validity of the scriptures with the approach of critics of sanad and the abuse. Additionally, the research examines methodological differences in the hadiths selection. It is a qualitative study with an approach to literature (library research). Based on analysis, the differences in the purpose of writing are reflected in the differences in the validity of the hadiths in the two books. This study affirms the importance of understanding the context of methodologies of classical methodology. As for the purpose, it is to rate the mortality rate of history more proportionately.